Blood mercury concentrations in four sympatric gull species from South Western France: Insights from stable isotopes and biologging. (1st September 2022) - Jouanneau, William; Sebastiano, Manrico; Rozen-Rechels, David; Harris, Stephanie M.; Blévin, Pierre; Angelier, Frédéric; Brischoux, François; Gernigon, Julien; Lemesle, Jean-Christophe; Robin, Frédéric; Cherel, Yves; Bustamante, Paco; et al.
Abstract: Mercury (Hg) is a toxic trace element widely distributed in the environment, which particularly accumulates in top predators, including seabirds. Among seabirds, large gulls ( Larus sp) are generalist feeders, foraging in both terrestrial and marine habitats, making them relevant bioindicators of local coastal Hg contamination. In the present study, we reported blood Hg concentrations in adults and chicks of four different gull species breeding on the French Atlantic coast: the European herring gull ( Larus argentatus ), the Lesser black-backed gull ( L. fuscus ), the Great black-backed gull ( L. marinus ) and the Yellow-legged gull ( L. michahellis ). We also investigated the potential role of foraging ecology in shaping Hg contamination across species, using the unique combination of three dietary tracers (carbon, nitrogen and sulfur stable isotopes) and biologging (GPS tracking). A high concentration of Hg was associated with high trophic position and a marine diet in gulls, which was corroborated by birds' space use strategy during foraging trips. Adults of all four species reached Hg concentrations above reported toxicity thresholds. Specifically, adults of Great black-backed gulls had a high trophic marine specialized diet and significantly higher Hg concentrations than the three other species. Blood Hg was 4–7 times higher in adults than in chicks, although chicks of all species received mainly marine and high trophic position prey, which is expected to be the cause of blood Hg concentrations of toxic concern. By using both stable isotopes and GPS tracking, the present study provides compelling insights on the main feeding habits driving Hg contamination in a seabird assemblage feeding in complex coastal environments. Graphical abstract: Image 1 Highlights: Hg was measured in adults and chicks of four sympatric species of gulls. Hg concentrations widely varied among the four investigated species. Hg was higher in birds feeding on high trophic position and marine prey. Chicks were fed almost exclusively with a marine diet of high trophic position. Hg exceeded reported toxicity thresholds in some adults of all four species.